Cercis: A Non-polyploid Genomic Relic Within the Generally Polyploid Legume Family - Stai, Jacob S.; Yadav, Akshay; Sinou, Carole; Bruneau, Anne; Doyle, Jeff J.; Fernández-Baca, David; Cannon, Steven B. (Frontiers in Plant Science, 2019)
Based on evolutionary, phylogenomic, and synteny analyses of genome sequences for more than a dozen diverse legume species as well as analysis of chromosome counts across the legume family, we conclude that the genus Cercis provides a plausible model for an early evolutionary form of the legume genome. The small Cercis genus is in the earliest-diverging clade in the earliest-diverging legume subfamily (Cercidoideae). The Cercis genome is physically small, and has accumulated mutations at an unusually slow rate compared to other legumes. Chromosome counts across 477 legume genera, combined with phylogenetic reconstructions and histories of whole-genome duplications, suggest that the legume progenitor had 7 chromosomes – as does Cercis. We propose a model in which a legume progenitor, with 7 chromosomes, diversified into species that would become the Cercidoideae and the remaining legume subfamilies; then speciation in the Cercidoidea gave rise to the progenitor of the Cercis genus. There is evidence for a genome duplication in the remaining Cercidoideae, which is likely due to allotetraploidy involving hybridization between a Cercis progenitor and a second diploid species that existed at the time of the polyploidy event. Outside the Cercidoideae, a set of probably-independent whole-genome duplications gave rise to the five other legume subfamilies, at least four of which have predominant counts of 12-14 chromosomes among their early-diverging taxa. An earlier study concluded that independent duplications occurred in the Caesalpinioideae, Detarioideae, and Papilionoideae. We conclude that Cercis may be unique among legumes in lacking evidence of polyploidy, a process that has shaped the genomes of all other legumes thus far investigated.